Research note: A low-density SNP genotyping panel for Chinese native chickens - Jie Wang; Siyuan Xing; Yan Zhou; Jie Liu; Yan Sun; Qiuxia Lei; Haixia Han; Wei Liu; Dapeng Li; Fuwei Li; Dingguo Cao (Poultry Science)
The efficiency of molecular breeding largely depends on the cost of genotyping, which plays an important role in breeding and population genetic studies. Compared to pig, cattle, and sheep, poultry has a small size genome, and lower individual value. Developing a relatively low-density genotyping panel is needed to decrease the genotyping cost for poultries. In the present study, we developed a chicken 11 K single nucleotide polymorphism (SNP) genotyping panel for breeding and genetic analysis using genotyping by targeted sequencing (GBTS). The panel design was based on whole genome sequencing data from 7 local breeds and a commercial breed. In total 11,200 SNPs were included in the final chip. Population analyses of the eight breeds showed high SNP call rates and minor allele frequencies (MAF), enabling clear differentiation between populations. The families within population can also be identified. Additionally, the 11K panel was applied to a genomic prediction of Wenshang Barred chickens, the predictive ability and prediction accuracy between the WGS and chip dataset non-significantly differed. Therefore, the newly developed chicken low-density SNP is efficient, cost-effective, and well-suited for application in local Chinese chickens, which can accelerate chicken breeding improvements and enhance conservation efforts.